KOMUNIKASI INTRAPERSONAL REMAJA DALAM MENCEGAH KECANDUAN SMARTPHONE UNTUK MENJAGA KESEHATAN MENTAL - Ronauli Sagala (2023)
This study discusses the intrapersonal communication that occurs in adolescents who face smartphone addiction. This study aims to provide knowledge to adolescents so that they can maintain their mental health by dealing with problems that may arise as a result of smartphone addiction using intrapersonal communication. This study uses a qualitative method with a phenomenological approach. To assist the research, the intrapersonal communication theory model popularised by Rakhmat and attribution theory was also used. The results of this study found that intrapersonal communication occurs in adolescents to help them decide to stop or not use smartphones and adolescents are able to maintain their mental health by having good intrapersonal communication.